Odpowiedzi

Najlepsza Odpowiedź!
2009-11-22T12:46:59+01:00
0.3 -[(-¼)×6+(-dwie piąte) × (pietnaście czwartych)] ×[-1-(-½) × (-¼)]+ 2½=....

= 3/10- [ (-¼) *6 + (-2/5)*(15/4)]*[ -1 -(-½)*(-¼)] +5/2 =
= 3/10 -[- 3/2 +(-3/2)]*[ -1-⅛] +5/2 =
= 3/10 - [-3/2 -3/2]*[(-9/8)] +5/2 =
= 3/10 - [(- 3)*(-9/8)] + 5/2 =
= 3/10 -( 27/8) + 5/2 =
= 12/40 -135/40 + 100/40 =
= -23/40
2009-11-22T12:47:40+01:00
0,3-[(-1/4)*6+(-2/5)*(15/4)]*[-1-(-1/2)*(-1/4)] + 5/2=
3/10 -[(-3/2)-3/2]*[-1-1/8]+5/2=
3/10-[-6/2]*[-9/8]+5/2=
3/10-27/8+5/2=
12/40-135/40+100/40=-23/40


2009-11-22T12:54:43+01:00
0,3 - [(-3/2) - 3/2] * [-1 - ⅛] + 2½ = 0,3 - [-6/2 * (-9/8)] + 2½ = 0,3 - 27/8 - 2½ = 3/10 - 27/8 + 5/2 = 12/40 - 135/40 + 100/40 = 112/40 - 135/40 = - 23/40

Odpowiedź jest prawidłowa w 100%!